1995
DOI: 10.1128/jcm.33.7.1915-1916.1995
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of sputum by cytocentrifugation for preparation of smears for detection of acid-fast bacilli does not increase sensitivity of the fluorochrome stain

Abstract: To evaluate the usefulness of cytocentrifugation for detection of acid-fast bacilli (AFB) in sputum specimens, we compared this method to a traditional concentration method for the preparation of smears. A total of 844 sputum specimens (from 579 patients) of adequate volume that were submitted for detection of mycobacteria were evaluated. A portion of each specimen was used for cytocentrifugation; the remainder was processed by our decontamination-concentration protocol (2% sodium hydroxide-N-acetyl-L-cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Recently, Saceanu et al reported that for sputum specimens from a selected group of patients, the sensitivity of AFB microscopy with the Kinyoun stain was greatly improved by using cytocentrifugation for smear preparation (154). This finding, however, was not confirmed in a more extensive evaluation in which auramine O was used for visualization of AFB (201).…”
Section: Stains For Detection Of Mycobacteriamentioning
confidence: 99%
“…Recently, Saceanu et al reported that for sputum specimens from a selected group of patients, the sensitivity of AFB microscopy with the Kinyoun stain was greatly improved by using cytocentrifugation for smear preparation (154). This finding, however, was not confirmed in a more extensive evaluation in which auramine O was used for visualization of AFB (201).…”
Section: Stains For Detection Of Mycobacteriamentioning
confidence: 99%
“…A study conducted in France found cytocentrifugation using disposable chambers to give excellent results if one considers cellularity, fixation and the comfort for screening and also found it to be cost efficient when compared to other techniques like Cytyc Thinprep liquid-based cytology technique [4]. Another study done in Department of Pathology, University of Texas, Medical branch on sputum specimens for the detection of AFB discusses the added expense of cytocentrifugation for routine concentration of sputum specimens for the preparation of smears for detection of AFB and found cytocentrifugation to be useful when immediate preparation of a smear for the detection of AFB is requested, especially when the equipment is already available [11]. Also, another study conducted by Saceanu and coworkers concluded the presence of consistently higher number of cells on Cyto-Tek positive smears compared to parallel smears made by the traditional smear preparation technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…For many years the AFB smear, results of which are available in 24 h or less, has been the only rapid diagnostic test available. Unfortunately the AFB smear is not an especially sensitive test nor is it specific for tuberculosis (13). Therefore, a laboratory test with performance characteristics that are superior to those of the AFB smear but with a similar turnaround time is needed.…”
Section: Discussionmentioning
confidence: 99%